Step-by-step explanation
We must solve the following equation for x:
![x+3=√(3-x)](https://img.qammunity.org/2023/formulas/mathematics/college/4v7paahs8x0mcv4cb2x9l8jfu0rczwhdo7.png)
We can square both sides of the equation so we can get rid of the radical:
![\begin{gathered} (x+3)^2=(√(3-x))^2 \\ (x+3)^2=3-x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/khkqueva69o1remm4mdmwozry1orncxv38.png)
We expand the squared binomial on the left:
![\begin{gathered} (x+3)^2=x^2+6x+9=3-x \\ x^2+6x+9=3-x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bpgqblu32a6fzorzf4g0u0nbanfy9czhrb.png)
Then we substract (3-x) from both sides:
![\begin{gathered} x^2+6x+9-(3-x)=x-3-(3-x) \\ x^2+6x+9+x-3=0 \\ x^2+7x+6=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3sxq7upxwvqw2pxhlens8ltdxjh8oxikce.png)
Then we have to find the solutions to this last equation. Remember that the solutions to an equation of the form ax²+bx+c have the form:
![x=(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/jr19ixi2zltkocy82qhxfiop5lyv4hzbkm.png)
In our case a=1, b=7 and c=6 so we get:
![\begin{gathered} x=(-7\pm√(7^2-4\cdot1\cdot6))/(2\cdot1)=(-7\pm√(49-24))/(2)=(-7\pm√(25))/(2)=(-7\pm5)/(2) \\ x=(-7+5)/(2)=-1\text{ and }x=(-7-5)/(2)=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eehoo77wv221f3mbj8vgpjvixci3yrzagm.png)
So we have two potential solutions x=-1 and x=-6. However we should note something important, in the original equation we have the term:
![√(3-x)](https://img.qammunity.org/2023/formulas/mathematics/college/lkght7oqyju4ytg4tki84592x6cb6iep2g.png)
Remember that the result of the square root is always positive. Then the term in the left of the expression has to be positive or 0. Then we impose a restriction in the value of x:
![x+3\ge0\rightarrow x\ge-3](https://img.qammunity.org/2023/formulas/mathematics/college/43ron2zscmhajzgz2dgkxa6lc1lilditny.png)
From the two possible solutions only x=-1 is greater than or equal to -3 so this is the correct one.
Answer
Then the answer is option A.